PENINGKATAN KREATIVITAS GURU MELALUI PENGEMBANGAN SERVANT LEADERSHIP DAN EFIKASI DIRI GURU TETAP YAYASAN - Andri Sudrajat; Sri Setiyaningsih; Eri Sarimanah (Universitas Pakuan, 2020)
IMPROVING TEACHER CREATIVITY THROUGH THE DEVELOPMENT OF SERVANT LEADERSHIP AND SELF EFFICATIONTeacher creativity is the teacher's ability to create new things in teaching so that they have variations in teaching that driving students to be more active and creative. In essence, if teaching is carried out properly, it can be said to be creative. The key to the success of creative development lies in teaching creatively and efficiently in conducive interactions. This is not easy and requires expertise and creativity in learning activities to achieve what is expected. This study aims to point out efforts to increase teacher creativity through an examination of the relationship between research variables, namely the relationship between servant leadership and teacher creativity, the relationship between self-efficacy and teacher creativity, the relationship of both servant leadership and self-efficacy with teacher creativity. The study was conducted using correlational statistical methods to determine whether other variables, namely servant leadership and self-efficacy have a positive relationship with teacher creativity. The research was conducted to the permanent teachers of the SMP Foundation throughout Cigudeg District, Bogor Regency with a population of 267 and a sample of 159 teachers. The results showed that there was a very strong and very significant positive relationship between servant leadership and teacher creativity with a correlation coefficient ρyx1 = 0.983; there is a very strong and very significant positive relationship between self-efficacy and teacher creativity with a correlation coefficient ρyx2 = 0.980, and there is a very strong and very significant positive relationship both servant leadership and self-efficacy together with teacher creativity with the correlation coefficient ρyx3 = 0.989. This evidence shows that teacher creativity can be increased through servant leadership and self-efficacy.